Use of planning parameters within Rolls-Royce: investigation of enablers and barriers for inventory reductions. - Hüfner, Claudia (2009)
Rolls-Royce plc is a global business that provides and supplies integrated power systems for use at sea, on land and in the air. Civil Aerospace, Defence Aerospace, Marine and Energy are the areas in which the Group has established a strong position. The company received higher orders in the past few years and annual sales were £9.1 billion in 2008. However, Rolls-Royce aims at a reduction of its inventory levels as the company maintains that its current performance for inventory management is below the industry norm. This dissertation will investigate how the current use of planning parameters within Rolls-Royce supports the company to achieve its aim. The project aims at identifying areas of improvement in the performance of lead time management in the company’s Enterprise Resource Planning (ERP) system and pursues a combination of internal and external benchmarking.